2001
DOI: 10.1172/jci10360
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deaminase deficiency increases thymic apoptosis and causes defective T cell receptor signaling

Abstract: Adenosine deaminase (ADA) deficiency in humans results in a severe combined immunodeficiency (SCID). This immunodeficiency is associated with severe disturbances in purine metabolism that are thought to mediate lymphotoxicity. The recent generation of ADA-deficient (ADA -/-) mice has enabled the in vivo examination of mechanisms that may underlie the SCID resulting from ADA deficiency. We demonstrate severe depletion of T and B lymphocytes and defects in T and B cell development in ADA -/-mice. T cell apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 35 publications
7
65
0
Order By: Relevance
“…dATP accumulation interferes with DNA replication and notably can promote apoptosis by stimulating "apoptosome" assembly through the formation of a specific complex containing dATP, cytoplasmic cytochrome c, Apaf-1, and caspase 9 [32][33][34] . Experiments performed in ADA-deficient mice and in murine fetal thymic organ culture indicate that apoptosis is an important component of disease pathogenesis [24,35]. Although we did not observe "active problems" at the time of Annexin V measurement that could have influenced the results, we found a significant number of cells in an early stage of apoptosis, suggesting that this can be a mechanism contributing to the T cell lymphopenia observed in our ADA-SCID patients treated with PEG-ADA.…”
Section: Discussionmentioning
confidence: 54%
“…dATP accumulation interferes with DNA replication and notably can promote apoptosis by stimulating "apoptosome" assembly through the formation of a specific complex containing dATP, cytoplasmic cytochrome c, Apaf-1, and caspase 9 [32][33][34] . Experiments performed in ADA-deficient mice and in murine fetal thymic organ culture indicate that apoptosis is an important component of disease pathogenesis [24,35]. Although we did not observe "active problems" at the time of Annexin V measurement that could have influenced the results, we found a significant number of cells in an early stage of apoptosis, suggesting that this can be a mechanism contributing to the T cell lymphopenia observed in our ADA-SCID patients treated with PEG-ADA.…”
Section: Discussionmentioning
confidence: 54%
“…In line with our B cell findings, other studies have shown proliferation and activation signaling defects in T cells under conditions of ADA deficiency. For instance, ADA-deficient peripheral T cells have shown a reduction of tyrosine phosphorylation of TCR-associated signaling molecules and a block of TCRmediated calcium flux (17). Also, extracellular adenine nucleotides, which accumulate in ADA deficiency, inhibit CD4 ϩ T cell activation via an increase in cAMP induced by an unidentified purinergic receptor (29).…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of the B cell compartment in the bone marrow of ADA-deficient mice was initiated to determine whether, in analogy to T cell development, a blockade in B cell lymphopoiesis exists (5,16,17). The developmental parallels showed by B and T cells, including gene rearrangement and selection, suggested that ADA deficiency, with a block in early T cell development, could equally affect the early B cell maturation program.…”
Section: B Cell Development In Bone Marrow Is Not Impaired In Ada-defmentioning
confidence: 99%
“…In the initial article by Apasov et al (27), ADA deficiency without PEG-ADA injection showed greater thymic apoptosis with a relatively normal peripheral lymphocyte distribution. To characterize any potential immunological defects with the maintenance of PEG-ADA, 4-wk-old thymic and splenic populations were analyzed for T and B cell markers.…”
Section: Characterization Of D20 Nod Micementioning
confidence: 99%